с уравнением
(5x-4)(6-x)=0

НатаЛини НатаЛини    3   20.05.2021 09:35    0

Ответы
svsand svsand  19.06.2021 09:36

4/5,6

Пошаговое объяснение:

5x-4=0 или 6-x=0

5x=4 или -x=-6

x=4/5 или x=6

ПОКАЗАТЬ ОТВЕТЫ
Romangritsak13 Romangritsak13  19.06.2021 09:36

x_1 = \frac{4}{5}\\x_2 = 6

Пошаговое объяснение:

:

(5x-4)(6-x)=0\\5x*6-5x*x-(4*6-4*x)=0\\30x-5x^2-(24-4x)=0\\30x-5x^2-24+4x=0\\-5x^2+34x-24=0

Теперь через дискриминант:

D=b^2-4ac=34^2-4*(-5)*(-24)=1156-480=676\\\sqrt{D} = \sqrt{676} = 26\\x_{1,2} = \frac{-b+-\sqrt{D} }{2a} =\frac{-34+-26}{2*(-5)}=\frac{-34+-26}{-10} \\x_1=\frac{-34+26}{-10} =\frac{-8}{-10} = \frac{4}{5} \\x_2=\frac{-34-26}{-10} = \frac{-60}{-10} = 6

:

(5x-4)(6-x)=0\\\left \{ {{5x-4=0} \atop {6-x=0}} \right.\\\left \{ {{5x=4} \atop {-x=-6}} \right. \\\left \{ {{x=\frac{4}{5}} \atop {x=6}} \right.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика